2019
DOI: 10.1007/s11606-019-05269-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a Patient-Centered Behavioral Economics Intervention on Hypertension Control in a Highly Disadvantaged Population: a Randomized Trial

Abstract: BACKGROUND: Uncontrolled hypertension contributes to disparities in cardiovascular outcomes. Patient intervention strategies informed by behavioral economics and social psychology could improve blood pressure (BP) control in disadvantaged minority populations. OBJECTIVE: To assess the impact on BP control of an intervention combining short-term financial incentives with promotion of intrinsic motivation among highly disadvantaged patients. DESIGN: Randomized controlled trial. PARTICIPANTS: Two hundred seven ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 55 publications
(49 reference statements)
0
18
0
Order By: Relevance
“…Health education from well informed community health workers has indeed became a factor that improved hypertensive patients practice on hypertension self-management such as medication adherence and low salt diet compliance. [ 11 13 15 17 18 19 20 21 ] In this study, the proportion of hypertensive patients' with good medication adherence and low salt diet compliance were increased after health education on community health worker. It showed that community health workers were able to affect the hypertensive patients' behavior in the community.…”
Section: Discussionmentioning
confidence: 67%
“…Health education from well informed community health workers has indeed became a factor that improved hypertensive patients practice on hypertension self-management such as medication adherence and low salt diet compliance. [ 11 13 15 17 18 19 20 21 ] In this study, the proportion of hypertensive patients' with good medication adherence and low salt diet compliance were increased after health education on community health worker. It showed that community health workers were able to affect the hypertensive patients' behavior in the community.…”
Section: Discussionmentioning
confidence: 67%
“…Financial incentives are proven to induce changes in health-related behavior, such as smoking cessation, weight loss, glycemic control, and hypertension control, thereby aiding in disease management. 11 , 14 , 16 , 17 , 24 , 25 Nevertheless, providing financial incentives to patients with hypertension is not always effective. Kaboli et al 11 used 3 interventions to encourage patients to talk to their doctors about antihypertensive medication intensification.…”
Section: Discussionmentioning
confidence: 99%
“…After 12 months, improved BP control was evident only in the group receiving all 3 interventions. Shapiro et al 14 offered intervention participants a combination of fixed payments, contingent payments, and lotteries (eg, payment per mm Hg of improved BP, or a lottery card, to meet the health goals set by the researchers) in a highly disadvantaged minority population. This study revealed that financial incentives for measuring home BP aid in achieving short-term improvement in systolic BP control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…S hapiro and colleagues assessed the efficacy of an intervention that combines monetary incentives and promotion of intrinsic motivation to improve blood pressure (BP) control among low-income and racial/ethnic minority patients. 1 Uncontrolled hypertension is a leading cause of premature death in these subgroups. 2 The investigators found short-term improvements in BP control at 6 months when the incentives ended, although the effects had largely faded by 12 months.…”
mentioning
confidence: 99%